SISTEM INFORMASI MONITORING HELPDESK PADA PT. KRAMA YUDHA RATU MOTOR DENGAN METODE WATERFALL - KEZALDO KEZALDO; MUCHLISIN SYAHRI (Jupiter: Journal of Computer & Information Technology, 2021)
The design of the helpdesk monitoring information system is made to assist in handling problems in the production system at PT. Krama Yudha Ratu Motor (KRM) to IT Support staff, both software and hardware problems, the information system currently running in the company is still deemed inadequate because every time there is a request to repair a problem in production it has not been recorded in the database and is difficult to monitor and monitor. further analyzed by superiors, especially those related to the use of spare parts, on the other hand the staff officer also experienced difficulties in checking the tasks that were being and had been carried out by the personnel if there was a question from the superior of theproduction team who submitted a request for repair.